Sources of Information about Dietary Fibre: A Cross-Country Survey - Ferreira, M. (2016)
Dietary fibre (DF) has been recognized as a major determinant for improvement of health. Hence the means of information through which people become aware of its benefits are crucial. This work aimed at studying the sources of information about DF, as a means to educate people about aspects related to healthy eating. Factors such as gender, level of education, living environment or country were evaluated as to their effect on the selection of sources and preferences. For this, a descriptive cross-sectional study by means of a questionnaire, applied to a non-probabilistic sample of 6010 participants from 10 countries in different continents (Europe, Africa and America), answered after informed consent by all participants. For the analysis were used several descriptive statistics tools, crosstabs and chi square test to assess the relations between some of the variables under study. The results showed that mostly the information about DF comes from the internet, but the participants recognize that television might be a most suitable way to disseminate information about DF. The results also indicated differences between genders, levels of education, living environments and countries. The internet, the preferred source of information, got highest scores for Hungary, for urban areas, for university level of education and for female gender. The radio, the least scored source of information, was preferred in Egypt, for men and with lower education (primary school). As a conclusion, people get information through the internet due to easy access. However, it is to some extent a risk given the impossibility to control de information made public on the internet. The role of health centers and hospitals as well as schools should definitely be increased, as a responsible way to ensure correct information.